2018
DOI: 10.1002/advs.201801026
|View full text |Cite
|
Sign up to set email alerts
|

The Dawn of Single Material Organic Solar Cells

Abstract: Single material organic solar cells (SMOSCs) are based on ambivalent materials containing electron donor (D) and acceptor (A) units capable to ensure the basic functions of light absorption, exciton dissociation, and charge transport. Compared to bicomponent bulk heterojunctions, SMOSCs present several major advantages such as considerable simplification of cell fabrication and a strong stabilization of the morphology of the D/A interface, and thus of the cell lifetime. In addition to these technical issues, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
106
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 136 publications
(448 reference statements)
0
106
0
Order By: Relevance
“…Over the past two decades, several research groups, including our own, have been studying new materials that covalently anchor the electron donor (D) and acceptor (A) moieties . PSCs bearing above‐mentioned materials have recently been studied in two main forms.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, several research groups, including our own, have been studying new materials that covalently anchor the electron donor (D) and acceptor (A) moieties . PSCs bearing above‐mentioned materials have recently been studied in two main forms.…”
Section: Introductionmentioning
confidence: 99%
“…[7,14] Single-component OSCs (SCOSCs) promise a simpler device fabrication and a potential solution to the morphological instability of many bulk heterojunction OSCs. [15] SCOSCs do not rely on charge separation at a heterojunction and vivid research has been performed to enhance in the efficiency of those systems by increasing their dielectric constant, exploiting bulk ionization effects or utilizing block copolymers that combine donor and acceptor moieties to facilitate the dissociation of excitons. [16][17][18] Among others, Chandran et al have reported the direct free carrier generation in SCOSCs employing the small molecule chloroboron subnaphthalocyanine (SubNc), which reached an EQE of 22% despite the absence of an acceptor molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Thed ouble-cable conjugated polymer is one of the most important material categories for single-component organic solar cells (SCOSCs), [1] in which the electron-accepting segments are covalently linked to the conjugated donor polymers to guarantee the intramolecular charge transfer from donor to acceptor.T his is an elegant approach to overcome the limitation of conventional bulk-heterojunction organic solar cells (BHJOSCs). First, the device fabrication process will be greatly simplified since the photoactive layer contains only one single material.…”
Section: Introductionmentioning
confidence: 99%